2013
DOI: 10.1371/journal.pone.0080656
|View full text |Cite
|
Sign up to set email alerts
|

A Balanced IL-1β Activity Is Required for Host Response to Citrobacter rodentium Infection

Abstract: Microbial sensing plays essential roles in the innate immune response to pathogens. In particular, NLRP3 forms a multiprotein inflammasome complex responsible for the maturation of interleukin (IL)-1β. Our aim was to delineate the role of the NLRP3 inflammasome in macrophages, and the contribution of IL-1β to the host defense against Citrobacter rodentium acute infection in mice. Nlrp3−/− and background C57BL/6 (WT) mice were infected by orogastric gavage, received IL-1β (0.5 µg/mouse; ip) on 0, 2, and 4 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 59 publications
1
35
0
Order By: Relevance
“…Chung and colleagues demonstrated that IL1β signaling drives an early TH17 differentiation [47]. In addition it was shown that balanced IL1β activity is required for the host response to C. rodentium infection as IL1β improved the bacterial clearance but also increased tissue damage [48]. These results are in accordance with those of our study as we found that increased expression of IL17 and IL22 in the colon of C. rodentium -infected CD4-IL10ko mice was accompanied by elevated IL1β expression.…”
Section: Discussionmentioning
confidence: 99%
“…Chung and colleagues demonstrated that IL1β signaling drives an early TH17 differentiation [47]. In addition it was shown that balanced IL1β activity is required for the host response to C. rodentium infection as IL1β improved the bacterial clearance but also increased tissue damage [48]. These results are in accordance with those of our study as we found that increased expression of IL17 and IL22 in the colon of C. rodentium -infected CD4-IL10ko mice was accompanied by elevated IL1β expression.…”
Section: Discussionmentioning
confidence: 99%
“…Both NLRP3 and NLRC4 were shown to detect S. typhimurium (Broz et al , 2012Carvalho et al 2012), and IL-1b and IL-18 were found to be important for controlling S. typhimurium infection (Raupach et al 2006). Similar to S. typhimurium, C. rodentium infection results in NLRP3-and NLRC4-dependent inflammatory responses that limit bacterial burden and tissue pathology, which was proposed to be IL-18 dependent (Kayagaki et al 2011b;Gurung et al 2012b;Liu et al 2012a;Alipour et al 2013). Unlike for S. typhimurium, NLRP3 and NLRC4 were shown to sense C. rodentium in nonhematopoietic cells, most likely in intestinal epithelial cells Nordlander et al 2013;Song-Zhao et al 2013).…”
Section: Intestinementioning
confidence: 99%
“…In our previous work, we showed that extraneous IL-1β improves the ability of macrophages to phagocytose C. rodentium in Nlrp3 -/- mice and that clearance of infection is dependent on the NLRP3 inflammasome [20]. As an extension of these findings, we aimed to optimize bacterial handling and hypothesized that increasing inflammasome activation would also improve the ability of macrophages to kill these pathogens.…”
Section: Introductionmentioning
confidence: 99%